Environmental-friendly countermeasures applied to control instabilities in a high vertical rock slope: an example from Oita prefecture, Japan - Bhattarai, Tara Nidhi (Journal of Nepal Geological Society, 2002)
An analytical method for the selection of countermeasures to control instabilities in a high vertical slope composed of welded tuff underlain by gravelly palaeo-channel deposit has been described. Based on the engineering geological investigation, discontinuity features namely, orientation, spacing and persistence representing the slope were established as input data for the DEM (distinct element method) model construction. The model analysis reveals that the studied slope is prone to sliding (slumping) accompanied by to toppling failure, which may cause disaster by blocking the river at the toe of the slope. Construction of a concrete base structure at the toe of the slope is suggested to restrict sliding (slumping). But toppling and sliding of individual rock blocks at the upper part of the slope are allowed to take place naturally. This arrangement ensures long-term safety as well as maintenance of natural environment to reasonable limits and will encourage the local authority to offer the site as a place of learning natural phenomena and its method of preservation.